2006
DOI: 10.1021/ma061032v
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Slurry-Phase Homopolymerization of Ethylene to Branched Polyethylenes Using α-Diimine Nickel(II) Catalysts Covalently Linked to Silica Supports

Abstract: R-Diimine nickel(II) complexes covalently linked to a silica support were obtained by the reaction of an amino-or hydroxy-functionalized R-diimine nickel complex with silica particles treated with trimethyl aluminum. These silica-supported aryl R-diimine nickel(II) precatalysts linked via an amino (1a) or hydroxy functionality (1b-c) at the p-aryl position, and precatalysts linked via one (2a) or two (2b) hydroxy functionalities in the alkyl backbone were used in slurry polymerizations of ethylene to produce b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 64 publications
2
51
0
Order By: Relevance
“…The nickel diimine complex, N2, is supposed to be covalently attached onto the TMA-treated silica. [16] Physiosorbed borates are assumed to activate the N2 complex, which was previously alkylated during treatment with TMA. Although the borate internal activator was physiosorbed onto the silica support, it is unlikely to be abstracted easily due to the poor solubility of borates in the hexane diluent, creating a very favorable supported catalyst for ethylene polymerization in slurry reactors.…”
Section: Ethylene Polymerization With Covalently Attached Supported Nmentioning
confidence: 99%
See 1 more Smart Citation
“…The nickel diimine complex, N2, is supposed to be covalently attached onto the TMA-treated silica. [16] Physiosorbed borates are assumed to activate the N2 complex, which was previously alkylated during treatment with TMA. Although the borate internal activator was physiosorbed onto the silica support, it is unlikely to be abstracted easily due to the poor solubility of borates in the hexane diluent, creating a very favorable supported catalyst for ethylene polymerization in slurry reactors.…”
Section: Ethylene Polymerization With Covalently Attached Supported Nmentioning
confidence: 99%
“…Recently, Brookhart's group showed that covalent bonding between nickel diimine catalysts and functional groups on the support surface allows higher nickel loadings, leading to high activity as well as strong catalyst immobilization on the support surface. [15,16] Alkyl aluminum activators, such as methyl aluminoxane (MAO), are effective catalysts activators but require Al/transition metal ratios that may vary from hundreds to thousands. Alternatively, bulky anionic borates such as B(C 6 F 5 ) À 4 can be used as activators and provide a more precisely defined catalyst system due to their exactly characterized structures.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that covalent linking of soluble metal complexes to the support was the most effective way to reduce leaching [30,31], and the negative influence on the active sites was relatively small. Schrekker et al [32] synthesized α-diimine nickel precatalysts with an amino or hydroxyl functionality at the р-aryl position and precatalysts with one or two hydroxyl functionalities in the alkyl backbone ( Figure 2). …”
Section: Late-transition-metal Catalysts Immobilized On Sio 2 Supportsmentioning
confidence: 99%
“…[ 25 , 26 ] Among them, nanoparticle supports may offer more advantages over bulk supports, such as increased surface area, mass transfer, and better heat and decreased internal surface area, [ 27 , 28 ] which made it in the use of slurry reactors. [ 29 ] Moreover, covalent linking of the soluble catalysts to the support is the most effective method to reduce the leaching phenomena. [ 19 ] In the case of olefin polymerization, steric crowding around the metal center and the growing polymer chain may lead to decreased activities, adverse mass transport effects, or both, [ 30 , 31 ] but the mechanism is still not clear, so there are a lot of works to do.…”
Section: Characterizationmentioning
confidence: 99%